Research into the effect of corporate culture on operational efficiency in the Turkish ready to wear industry - (:unkn) unknown (Lukasiewicz Research Network - Institute of Biopolymers and Chemical Fibres, 2011)
Corporate culture, which is acknowledged as a company's identity, has started to gain more importance with the developments in recent years. The main reason for a company forming a genuine culture is the effectiveness of the culture on business life, employees and costumer relations. It helps the firm to be well-known, and forms its values and relations with other organisations and individuals. Nowadays, the possibility of Turkish Ready to wear firms being able to compete both in national and international markets and being able to meet clients' "time, cost and quality" expectations is high. In this research, to reveal the relationship between corporate culture and operational efficiency in Turkish Ready to Wear industries, a survey was conducted amongst a total of 360 executives in 19 establishments, most of whom are in Istanbul. The results obtained were analysed using statistic package software - SPSS 16.0. for MS Windows.
Keywords: Corporate culture; Culture; Productivity; Ready to wear industry